NEW APPROACH TO FLARE GAS RECOVERY SYSTEM USING INTEGRATED RECIPROCATING COMPRESSORS FOR SOLVING ENVIRONMENTAL ISSUE BY MONETIZING GAS - Ratnayu Sitaresmi; Tamado Sitorus; Hari Karyadi Oetomo; Doddy Abdassah; Luluan Almanna Lubis (Universitas Trisakti, 2020)
Flare gas is light hydrocarbon gas, by product of any petroleum industry activities, that is flared; and it could not pass into production facilities due its to low pressure. The gas flare volume frequently is significant, causing greenhouse gas emissions which gives serious environmental issue. Aims: The purpose of this research is to utilize flare gas in oil and gas fields to reduce environmental issue. Methodology and Results: Flare gas in an oil producing field is compressed to produce higher pressure gas flow, by using three one-stage Integrated Reciprocating Compressors to enter the production trunk line. The gas is flown to CO2 Removal Plant, as the gas would be gas sales. The subject field in West Java, the production wells experiences pressure decline; resulting the wellhead flowing pressure becomes low, so the gas is being flared. The gas flare recovery system is economically profitable both for purchase and rental scenarios. Renting the equipment is more profitable and has lower technical risk, because all risks is burdened to rental service provider. Conclusion, significance and impact study: Monetizing flare gas will reduce environmental issue, and it is utilized for own use or gas sales. The best Economics Scenario is rental scenario.